TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN TANAMAN HIAS KAKTUS MELALUI PEMASARAN ONLINE DI CACTI HEAVEN BANDUNG - Salma Fauzia Kamila; Lucyana Trimo (Universitas Galuh, 2022)
Online marketing is not only applied to industrial products. Currently, the trend of buying and selling ornamental plants has penetrated the virtual world, one of which is cactus plants. Cacti Heaven is a cactus shop that has selling its products through online media. In order to reach and retain consumers, Cacti Heaven needs to provide the best products and services. This research aims to describe the characteristics of consumers and determine the level of satisfaction and customer loyalty of Cacti Heaven. Method that used on data processing are descriptive analysis, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and loyalty pyramids. The results showed that consumers were very satisfied with the performance of the attributes of Cacti Heaven with a CSI value of 86.40 percent. The results of the IPA analysis show that the attribute that is a priority for improvement is the provision of information. Cacti Heaven's consumer loyalty level has not been said to be loyal because the percentage of committed buyers is smaller than switcher buyers.